Upaya Tiongkok Dalam Mempertahankan Provinsi Xinjiang Ditengah Tekanan Internasional - Ryseldha Claudya Purba; Shary Charlotte Henriette Pattipeilohy (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The Chinese region has a diversity of tribes and cultures that are rarely known internationally. One of them is the Uyghurs which has recently received international attention. After Xinjiang was appointed as an autonomous region of China, relations between the Chinese government and the Uyghurs deteriorated since the emergence of the nationalist movement which made the situation in Xinjiang even more insecure. These nationalist movements include terrorism, separatism, and religious extremism. The purpose of this study is to provide another perspective in looking at the Xinjiang conflict which is from the point of view of the Chinese government. This study uses qualitative methods with secondary data sources, which are then analyzed using the concepts of National Interest, Hegemony, Conflict Dynamics, and theories of Conflict Causes. The results of this research indicate that the efforts of the Chinese government in maintaining hegemony in Xinjiang province are not for religious or cultural discrimination as is known by the international world, but rather are aimed at strengthening national interest namely maintaining regional security and preventing the development of nationalist movements by establishing the establishment of a Center for Education and Training Work